Influence of previous laparoscopic surgical and pathological diagnosis of endometriosis on pregnancy outcomes in women with adenomyosis - Zhao Tian; Jin Lai; Qing-Jie Zhai; Yi Li; Yue Wang; Xiao-Hong Chang; Hong-Lan Zhu; Heng Cui (Gynecology and Obstetrics Clinical Medicine, 2022)
Objectives: Previous studies demonstrated that endometriosis and adenomyosis are closely linked to lots of adverse pregnancy outcomes while the role of endometriosis in pregnant women with adenomyosis has not been explored yet. The present study aimed to evaluate the influence of previous laparoscopic surgical and pathological diagnosis of endometriosis on pregnancy outcomes in women with adenomyosis. Methods: A total of 60 pregnant women who were diagnosed with adenomyosis before or during pregnancy were included in this study. Among them, 8 were also diagnosed with endometriosis by previous laparoscopic surgery. The demographic characteristics and pregnancy outcomes were compared between women with adenomyosis only and those with the surgical history of endometriosis. Results: Compared with women with adenomyosis only, those concomitant with the surgical history of endometriosis had significantly higher age at delivery [37.5(36.25–39.75) vs. 35(33.25–37), P ​= ​0.016] and an increased risk of postpartum hemorrhage (PPH) (adjusted OR: 5.992, 95% CI: 1.03–34.857, P ​= ​0.046) while no significant differences were found in other adverse pregnancy outcomes between these two groups. Then we further detected the risk factor of PPH in women with adenomyosis and found that the surgical history of endometriosis (OR: 6.995, 95% CI: 1.16–42.171, P ​= ​0.034) and assisted reproductive technology (ART) (OR: 5.062, 95% CI: 1.494–17.146, P ​= ​0.009) were the parameters closely associated with the occurrence of PPH. Conclusions: The history of previous laparoscopic surgical and pathological diagnosis of endometriosis in pregnant women with adenomyosis may increase the risk of PPH, which still needs to be verified by future studies with a large sample size. Besides, pregnancy through ART is also an increased risk factor for PPH in women with adenomyosis. Pregnant women with adenomyosis who conceived with the surgical history of endometriosis or by ART should be closely monitored for the reason of being at high risk of PPH.